(3ef GdqQGgf Edi Gdeecfs - (3eUWai (B, (3Jjdhjfs ((3YeGf(B:s (3OGQ GdMGeO ddfTQ hGdJhRjY(B,s, 2021)
(3jgOa gPG GdcJGH Edi GSJcTGa Yeb GdCHMGK GdEHSJehdhLjI GdeYGUQI, eJJHkYG eSGQgG ef GdhGbY GdMGdj Edi BaGb GdeSJbHd GdeMJedI(B. (3jfbSe GdcJGH Edi NeSI eMGhQ QFjSjI JZWj LhGfH eJYOOI ef GdfXQjI GdeYQajI(B: (3GdeMhQ GdChd(B: (3jHOC GdcJGH HJMdjd eaGgje GdEHSJehdhLjG GdCSGSjI hGdYdGbGJ GdeJTGHcI ajeG HjfgG(B. (3jSYi gPG GdeMhQ Edi JhVjM cjajI JaGYd gPg GdeaGgje hJCKjQgG Ydi agefG ddYedjI GdeYQajI, hcja jecf dgPg GdeaGgje Cf JTcd CSGkSG eJjkfG dHfGA fXQjGJ eYQajI LOjOI(B.(3GdeMhQ GdKGfj hGdKGdK hGdQGHY(B: (3jJYeb GdcJGH aj JMdjd GdEHSJehdhLjG GdNGUI Hcd ef GdQjGVjGJ, hGdYdhe GdWHjYjI, hGdYdhe GdEfSGfjI(B. (3jSJYQV cd eMhQ Ydi MOI GdJMOjGJ hGdeaGgje GdaQjOI GdeQJHWI Hcd eLGd, hcja JSGge gPg GdeLGdGJ aj JTcjd agefG GdYGe ddeYQaI GdYdejI(B.(3GdeMhQ GdNGeS(B: (3jNJJe GdcJGH HJbOje bGFeI TGedI ef GdeQGLY hGdfeGPL GdJj jecf Cf Jchf eajOI ddbGQF GdQGZH aj JYejb OQGSJg aj eLGd GdEHSJehdhLjG(B. (3JSGge gPg GdeQGLY hGdfeGPL aj JhajQ QDjI ChSY hCcKQ JfhkYG ddehVhY(B.(3HTcd YGe, jbOe gPG GdcJGH OQGSI TGedI heJYebI ddEHSJehdhLjG GdeYGUQI, hjSYi Edi GdELGHI Ydi CSFdI LhgQjI Mhd WHjYI GdeYQaI, hcjajI GcJSGHgG, hcjajI JbjjegG(B.s
Keywords: (3GdCHMGK GdYdejI (B- (3GdadSaI s; (3GdEHSJjehdhLjGs; (3fXQjI GdeYQaIs